Pelatihan Project Based Learning Tentang â€œStek Tanamanâ€ di SMAS Attohiriyah Bodak untuk Meningkatkan Kemampuan Mahasiswa Magister Pendidikan IPA Universitas Mataram - Aris Doyan; Mahrus Mahrus; Susilawati Susilawati; Rahmat Rezki Aolia Akhzami; Yayuk Andayani; Muntari Muntari (Unram Journal of Community Service, 2023)
Project Based Learning is a student-centered learning model that builds and applies concepts in the final project by independently exploring and solving real-world problems. In this study, Project Based Learning learning was carried out by making learning videos about plant cuttings at SMAS ATTOHIRIYAH BODAK to improve students' existing competencies. The stages in this activity are the preparation stage which consists of identifying material and solutions for solving problems. Furthermore, the implementation stage consists of the process of making videos, video editing, and presentations. In the final stage, namely the evaluation and reporting stage which consists of evaluating learning videos and preparing activity reports. Based on the results of the activities that have been carried out, project based learning training activities are very useful for students, teachers and lecturers in developing their competencies to become facilitators in learning activities at the education unit level